Maximizing electronic resources management in libraries applying business process management - England, Lenore A.; Miller, Stephen D. (Chandos information professional series., 2016)
Business process management (BPM) can be beneficially applied to electronic resources management (ERM) to help organize processes in libraries. As an application, BPM for ERM leads to effective organizational changes. Maximizing Electronic Resources Management in Libraries takes this novel perspective by applying BPM principles and theories to ERM.